2018
DOI: 10.1111/1468-2427.12630
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages of Urban Leisure Culture in Inner‐City Bucharest

Abstract: Inner‐city redevelopment in the south‐eastern European metropolis of Bucharest has been an intriguing object of analysis. Having been neglected for a long time by its inhabitants, urban politics and the local economy, the historical inner city recently experienced tremendous development of its evening/night‐time economy and leisure culture, as though it had received fresh impulses from European integration. However, there is no single cause which effected this unexpected proliferation. Therefore, this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…have gradually disappeared under the impact of capitalism and globalization. The inner-city started to be neglected by urban politics and the local economy [54]. Other decisions or policies had an important contribution to the city center changes: the decline of the cultural function by closing public cinemas because of small investments in their modernization and the relocation of these services into private cinemas inside the malls [55]; low share of reconsolidated old buildings; difficult legislation or non-compliance with the legislation on the conservation of heritage buildings conducted to cases in which real estate developers have demolished heritage buildings without authorization [53]; the absence of legal obligations to maintain a proper degree of the condition and safety of buildings (some from the interwar period and nationalized, being occupied after 1945 by tenants for decades, including after the fall of the communist regime) and the fragile financial support through public programs of rehabilitation works or reconsolidation of those buildings with seismic risk.…”
Section: Case Study-bucharest City Center and The Context For Street ...mentioning
confidence: 99%
See 1 more Smart Citation
“…have gradually disappeared under the impact of capitalism and globalization. The inner-city started to be neglected by urban politics and the local economy [54]. Other decisions or policies had an important contribution to the city center changes: the decline of the cultural function by closing public cinemas because of small investments in their modernization and the relocation of these services into private cinemas inside the malls [55]; low share of reconsolidated old buildings; difficult legislation or non-compliance with the legislation on the conservation of heritage buildings conducted to cases in which real estate developers have demolished heritage buildings without authorization [53]; the absence of legal obligations to maintain a proper degree of the condition and safety of buildings (some from the interwar period and nationalized, being occupied after 1945 by tenants for decades, including after the fall of the communist regime) and the fragile financial support through public programs of rehabilitation works or reconsolidation of those buildings with seismic risk.…”
Section: Case Study-bucharest City Center and The Context For Street ...mentioning
confidence: 99%
“…The correlation between street art and socio-economic dynamics is hard to estimate. Burkner and Totelecan [54] demonstrated that it is not possible to verify the correlation between murals and increasing of residential market values in the real estate market in a district from Naples, but agreed that it has an impact on the social and physical sustainability of the place. Other authors focused, too, on their research on the sense of place and social capital [6].…”
Section: Case Study-bucharest City Center and The Context For Street ...mentioning
confidence: 99%
“…With the backing of the European Bank for Reconstruction and Development, as well as local investors, Lipscani's main corridor began gentrification in 2005 ( igloo 2005). By 2010, the neighbourhood had been transformed into a nighttime district catering to university students and professionals but also to foreign tourists (Bürkner & Totelecan 2018). Beyond the proliferation of upscale retail, restaurants, and bars, FDI funded the development of new residential and corporate offices in and around the city centre (Ion 2014).…”
Section: Outmentioning
confidence: 99%
“…The owners managed to regain all the buildings at 50 Vulturilor Street in 2002 and flipped the property for about 1.8 million Euros to a Norwegian real estate investor. His intention was to demolish the original structures and build luxury condominiums, a common form of new-build gentrification in Bucharest redrawing the class geography of its central neighborhoods (Davidson, 2018;Chelcea et al, 2015;Bürkner & Totelecan, 2018; see Figure 2). During the Global Financial Crisis of 2007 construction plans stopped, but the investor's lawyers managed to get eviction orders for all residents in 2014.…”
Section: The Birth Of the Vulturilor Street Campmentioning
confidence: 99%